New approach to diagnosis and treatment of Acanthamoeba keratitis – systematic review of literature - Kokot, Joanna; Dobrowolski, Dariusz; Lyssek-Boroń, Anita; Milka, Michał; Smędowski, Adrian; Wójcik, Łukasz; Wowra, Bogumił; Wylęgała, Edward (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Purpose: To present new methods of diagnosis and treatment of Acanthamoeba keratitis. Material and methods: Searching Medline base for articles in English publicated since 2006 till the beginning of 2011, describing the way and results of diagnosis and treatment Acanthamoeba keratitis. Publications include studies, reviews as well as case reports concerning discussed subject. Results: 14 publications were found and used to present miscellaneous methods utilized nowadays to identify the reason of Acanthamoeba keratitis with simultaneous evaluations of its’ sensitivity and specificity. The review comprises improvements of laboratory diagnosis as well as corneal imaging systems helpful to diagnose infectious keratitis. 17 publications were quoted to elaborate results of pharmacological protocols as well as surgical procedures of Acanthamoeba keratitis treatment. Outcomes of experimental investigations were also cited. Conclusions: As none of presented methods of diagnosis and treatment of Acanthamoeba keratitis have become a standardized guideline jet, still there is a great need to look for new ones.